2023
DOI: 10.1186/s13018-022-03487-6
|View full text |Cite
|
Sign up to set email alerts
|

Representation of women in orthopaedic surgery: perception of barriers among undergraduate medical students in Saudi Arabia

Abstract: Background While female participation has improved in several surgical specialties over time globally, no such increase has been observed in orthopaedic surgery over the past decades. The potential barriers to female participation are likely present from the beginning of medical education. Therefore, this study assessed the apparent lag in equal representation among men and women in orthopaedic surgery in the Kingdom of Saudi Arabia. Methods This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…This contradicted the report of Acai et al ( 2020), wherein medical students' preference for choosing a career as a general surgeon increased significantly after the sixth year, and the prevalence was higher in males [17]. Moreover, our study data indicates that female medical students are inclined towards selecting a general surgery specialty due to research opportunities, a less stressful environment, reduced working hours, and having family members in the same field [18]. In contrast, male students prioritize the social standing associated with the specialty.…”
Section: Discussioncontrasting
confidence: 99%
“…This contradicted the report of Acai et al ( 2020), wherein medical students' preference for choosing a career as a general surgeon increased significantly after the sixth year, and the prevalence was higher in males [17]. Moreover, our study data indicates that female medical students are inclined towards selecting a general surgery specialty due to research opportunities, a less stressful environment, reduced working hours, and having family members in the same field [18]. In contrast, male students prioritize the social standing associated with the specialty.…”
Section: Discussioncontrasting
confidence: 99%
“…Research has shown that approximately 80% of medical students in the U.K. have orthopaedic placements 81 in comparison with just 20% of those in the U.S. 82 , but the U.K. orthopaedic workforce is not appreciably more diverse than that of the U.S. In addition, a study found that clinical exposure did not significantly improve the likelihood of female medical students choosing orthopaedic surgery as a career in Saudi Arabia 47 .…”
Section: Resultsmentioning
confidence: 98%
“…45 A study of attitudes in the U.K. found that 24% of female medical students would consider a career in orthopaedic surgery 46 . In comparison, that rate was found to be 11% among female medical students in Saudi Arabia 47 . Surveys of medical students and of junior doctors have shown that perceived structural and cultural barriers may contribute to a reduced likelihood of applying to orthopaedics 48,49 .…”
Section: Global Diversity In Orthopaedicsmentioning
confidence: 88%